The Influence Of Hotel Tax, Restaurant Tax, Entertainment Tax And Advertising Tax On Local Revenue Of Sukabumi City Government In 2018-2022 (Case Study On The Sukabumi City Financial And Revenue Management Agency): - Nuraisah, Risa; Tanjung, Hendra; Indrawan, Andri (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the influence of hotel tax, restaurant tax, entertainment tax and advertising tax on local revenue. The variables used in this study are Hotel Tax (X1), Restaurant Tax (X2), Entertainment Tax (X3), Advertising Tax (X4) and Local Revenue (Y). Hotel Tax, Restaurant Tax, Entertainment Tax, and Advertising Tax are four important sources of income for local governments in increasing Local Revenue. The research method used is a quantitative method with an associative approach. The data used is secondary data obtained from the Sukabumi City Financial and Revenue Management Agency. The results of the study using SPSS 26, show that the effect of Hotel Tax on Local Original Income is tcount -0.036 <ttable 2.0067 with a sig value of 0.971> 0.05, which means that Hotel Tax partially has no effect and is not significant on Local Original Income. The effect of Restaurant Tax on Local Original Income is tcount -0.492 <ttable 2.0067 with a sig value of 0.624> 0.05, which means that Restaurant Tax partially has no effect and is not significant on Local Original Income. The effect of Entertainment Tax on Local Original Income is tcount 0.771 <ttable 2.0067 with a sig value of 0.444> 0.05, which means that Entertainment Tax has no effect and is not significant on Local Original Income. And the influence of Advertising Tax on Regional Original Income is tcount -0.343 <ttable 2.0067 with a sig value of 0.733> 0.05, which means that Advertising Tax has no effect and is not significant on Regional Original Income. The influence of Hotel Tax, Restaurant Tax, Entertainment Tax and Advertising Tax simultaneously is Fcount 0.214 <Ftable 2.55 with a sig value of 0.930> 0.05 and the coefficient of determination test shows that the contribution of Hotel Tax, Restaurant Tax, Entertainment Tax and Advertising Tax to Regional Original Income is 12.7% which means that Hotel Tax, Restaurant Tax, Entertainment Tax and Advertising Tax simultaneously have no effect and are not significant on Regional Original Income of Sukabumi City for the period 2018-2022.